PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SDN 034 TARAIBANGUN - Nova Mulia; Mahmud Alpusari; Lazim Lazim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the low learning outcomes of science subject "ilmu pengetahuan alam (IPA)” of students grade 5Ath of SDN 034 Taraibangun, with grade average 63,41, while the minimum exhaustiveness criteria "kriteria ketuntasan minimal (KKM)” for IPA is 70. Among 44 students, only 17 students who reached KKM with 38,64% classical completeness. This research used classroom action research "penelitian tindakan kelas" (PTK) on two cycles which aimed to improve IPA learning outcomes of students grade 5Ath of SDN 034 Taraibangun,by implementing contextual teaching and learning (CTL). The research subjects is students grade 5Ath SDN 034 Taraibangun. The research data were taken from observation and test. Data analysis technique used is descriptive statistical technique. The result of this research showed that the achievement of teacher activity in the first cycle 75%, and the second cycle is 93,75%. Students activities increased too. Students activities in first cycle is 62,5%, and the second cycle is 81,25%. Meanwhile, the average of IPA learning in the first cycle is 73,98 and in the second cycle is 76,82. Classical completeness in the first cycle is 65,91% increase to 86,36% in the second cycle. From this result it can be concluded that by apply CTL learning model in science studies can increase learning result of students in 5Ath grader class of SD N 034 Taraibangun.Keywords : contextual teaching and learning (CTL) model, IPA learning result